CircFBXL5 promotes breast cancer progression by sponging miR‐660. Issue 1 (15th November 2019) - Zhou, Huamao; Tang, Guohui; Zhao, Mi; Xie, Liming; Xie, Yuanjie; Zhang, Zhiwei; He, Xiusheng
Abstract: Increasing studies have revealed that circular RNAs (circRNAs) play important roles in cancer progression. However, the potential involvement of circRNAs in breast cancer metastasis to lung is not clear so far. In this study, we conducted circular RNA microarrays of primary breast cancer tissues and lung metastatic tissues. The results revealed that circFBXL5 (hsa_circ_0125597) up‐regulated the most in lung metastatic tissues. Survival analysis revealed that high levels of circFBXL5 correlated with worse outcome of breast cancer. Further experiments showed that knockdown of circFBXL5 inhibited breast cancer cell proliferation and migration to lung. Mechanism study showed that circFBXL5 acted as a sponge for miR‐660 and compete binding to miR‐660 with SRSF6, leading to increased expression of SRSF6. Collectively, our study highlighted the regulatory function of the circFBXL5/miR‐660/SRSF6 pathway in breast cancer progression, which could be potential therapeutic targets for breast cancer.